2014
DOI: 10.1111/jasp.12262
|View full text |Cite
|
Sign up to set email alerts
|

Economic indicators predict changes in college student optimism for life events

Abstract: This investigation explored the extent to which an economic recession predicted changes in college students' optimism about the length and quality of their futures. In a cross-sectional design, college students in the United States rated their likelihood of divorcing, being unhappy in their career, and living past age 60, at time points before, during, and in the aftermath of an economic recession (2007)(2008)(2009)(2010). Economic indicators, particularly gas prices, predicted decreased optimism as the indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…These affective events will influence diverse emotional reactions and consequent work-related attitudes and behaviors at work. For instance, some studies have shown that positive affective events are positively related with work engagement (Junça-Silva, Caetano, & Rueff-Lopes, 2017), job satisfaction (e.g., Ohly, & Smith, 2015), optimism (e.g., Lench, & Bench, 2014), among others. On the other hand, negative affective events have also been linked to decreased levels of work engagement (e.g., Junça-Silva, et al, 2017), physiological heath (Rueff-Lopes et al, 2017, optimism and relisience (e.g., Li, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These affective events will influence diverse emotional reactions and consequent work-related attitudes and behaviors at work. For instance, some studies have shown that positive affective events are positively related with work engagement (Junça-Silva, Caetano, & Rueff-Lopes, 2017), job satisfaction (e.g., Ohly, & Smith, 2015), optimism (e.g., Lench, & Bench, 2014), among others. On the other hand, negative affective events have also been linked to decreased levels of work engagement (e.g., Junça-Silva, et al, 2017), physiological heath (Rueff-Lopes et al, 2017, optimism and relisience (e.g., Li, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with several previous studies. Lench and Bench (2014) stated that college students exhibit less positivity towards future life events like professional career marriage, and after decline they exhibit an increasing future positivity. The elevated pressure triggered by poor financial situations and decreased positivity towards future exhibits the effect of financial stress on college students.…”
Section: Discussionmentioning
confidence: 99%